β-endorphin modulates the effect of stress on novelty-suppressed feeding - Barfield, Elizabeth T.; Moser, V. A.; Hand, Annie; Grisel, Judith (Frontiers in Behavioral Neuroscience, 2013)
Although stress is implicated in the pathophysiology of mood and anxiety disorders, not all individuals who suffer stressful life events develop psychopathology. Differential susceptibility to stress may be influenced by genetically mediated differences in hypothalamic-pituitary-adrenal (HPA) axis activity and moderation of the stress response by the opioid peptide β-endorphin (β-E). The present study investigated genetic contributions to coping behavior by examining anxious behavior of transgenic mice with varying capacities to synthesize β-E [B6.129S2-Pomctm1Low/J; regulated by insertion of a premature stop codon into one or both copies of the proopiomelanocortin (POMC) gene], both under normal conditions and following 3 min of forced swim (FS). Ten minutes after this stress exposure or a control manipulation, acutely food-deprived female and male transgenic mice were subjected to a novelty-suppressed feeding (NSF) test, during which their interaction with an almond slice located in the center of an open field box was measured. There was an interaction between genotype and stress for latency to approach the almond and whether or not the almond was approached, such that mice with low or absent β-E displayed a stronger aversion to novelty-feeding after stress exposure than did mice with normal levels. These data provide evidence for a moderating effect of β-E on the behavioral response to stress. Genotypic differences in anxious behavior emerged when mice were stressed prior to behavioral assessment, suggesting that β-E plays a role in coping behavior. These findings indicate that genetic variability in sensitivity of the β-E system to stress may contribute, at least in part, to heritable differences in stress reactivity as well as vulnerability to stress-related psychopathology.